The Philippine republic - Fernandez, Leandro Heriberto 1889-1948 (Studies in History, Economics, and Public Law Columbia university studies in the social sciences, 2019)
Studies the Philippine revolution, meaning the armed conflict which began as a revolt against Spain and ended as an act of resistance to the United States. Looks at the government and the political ideology of the movement.